Aproximações recentes entre construcionismo social e terapia no contexto acadêmico brasileiro - Focchi, Lívia de Arruda (2021)
Considering the growing diffusion of the social constructionism in Brazil in different areas of Psychology, this study had as general objective to analyze the approximations between therapy and social constructionism in the current brazilian academic context. To this end, a qualitative bibliographic study was developed that included the content analysis of 26 researches related to the dissemination of socio-constructionist therapies in the CAPES Theses and Dissertations Catalog, or in the PePSIC and/or SciELO platforms between 2010 and 2021. The results of analysis enabled the construction of the following thematic axes: 1) The dissemination of socio-constructionist therapies in the Brazilian academic context, 2) The constructionist movement in academia, and 3) What is this therapy?. It was possible to identify that the theme of constructionist therapies has been infrequently publicized in the investigated environment, mainly by psychologists who, in general, aimed at the analysis of different therapeutic approaches, concepts and techniques, therapeutic processes and their implications, as well as the diffusion of theories and techniques among family therapists. It was also noted that the analyzed studies are close to the speeches of Gergen, Anderson and McNamee, especially to think of the clinic as a social construction, confirming that different constructionist trends have been produced and disseminated in the country. In addition, the analysis allowed us to understand that the notions of therapy linked to constructionism are typically being associated with communication, relationship and changing the meanings of the problem, and that the reported practices were, above all, directed towards families and adults, under the influence Anderson and Goolishian's collaborative approach, Andersen's reflective processes, and White and Epston's narrative practices.